Antenna Array Bandwidth Enhancement using Polymeric Nanocomposite Substrate - W. A. W., Muhamad; R., Ngah; M. F., Jamlos; P. J., Soh; M. A., Jamlos; H., Lago (Springer, 2016)
A 4 × 2 array antenna is developed using a new nanocomposite polymeric magneto-dielectric substrate. The permittivity and permeability factors have been accounted in designing the proposed array antenna at the frequency of 2.6 GHz. A pure polydimethylsiloxane (P-PDMS) (ε r = 2.7) solution is mixed with ferrite III oxide (μ r = 1.2) to generate this new nanocomposite polymeric magneto-dielectric (NPMD) substrate. The NPMD surface is then hardened and located in between two P-PDMS layers. The 4 × 2 radiating elements are immersed to the top of P-PDMS layer, while SMA coaxial feeder is fed from underneath the ground layer. This sealing technique enabled the proposed antenna to be waterproof and flexible. This combination contributes to bandwidth enhancement of 52.65 %, size miniaturization of 176 × 156 mm2 and high gain of 10.8 dB. The measured results show a good agreement with simulations.